Application of digital image correlation technique to evaluate creep degradation of sealing elastomers due to exposure to fluids. (February 2018) - Farfán-Cabrera, Leonardo Israel; Pascual-Francisco, Juan Benito; Gallardo-Hernández, Ezequiel Alberto; Susarrey-Huerta, Orlando
Abstract: This work aims to evaluate degradation of viscoelasticity in terms of creep of four sealing elastomers (flouroelastomer/Viton A ®, silicon rubber/vinyl-methyl silicone, chloroprene rubber and ethylene-propylene-diene monomer) upon exposure to engine lubricant and diesel by using digital image correlation technique in a creep experiment for determination of changes in creep behavior of elastomers. Short creep experiments (3 h) were conducted under a tensile load of 1.5N before and after the immersion in the fluids. Also, standard compatibility tests were simultaneously conducted to determine changes in mass, volume, tensile and tearing strengths, and hardness to extend the degradation study. Hence, the creep compliance behavior of the samples was successfully obtained and the creep degradation due to immersion tests was determined. It was found that this alternative method for evaluation of creep degradation of elastomers is very suitable and useful since very low complexity and strain measurement accuracy. Highlights: Digital image correlation allowed the measurement of creep strains. Creep degradation of elastomers was evaluated by digital image correlation. Degradation of elastomers due to exposure to fluids was assessed. The creep experiments gave valuable information of degradation. The compatibility of elastomers with a lubricant and diesel was determined.